From financial crash to debt crisis - National Bureau of Economic Research, Cambridge; Reinhart, Carmen M.; Rogoff, Kenneth S. (Cambridge, MA, 2010)
"Newly developed long historical time series on public debt, along with modern data on external debts, allow a deeper analysis of the cycles underlying serial debt and banking crises. The evidence confirms a strong link between banking crises and sovereign default across the economic history of great many countries, advanced and emerging alike. The focus of the analysis is on three related hypotheses tested with both "world" aggregate levels and on an individual country basis. First, private debt surges are a recurring antecedent to banking crises; governments quite contribute to this stage of the borrowing boom. Second, banking crises (both domestic ones and those emanating from international financial centers) often precede or accompany sovereign debt crises. Indeed, we find they help predict them. Third, public borrowing accelerates markedly ahead of a sovereign debt crisis; governments often have "hidden debts" that far exceed the better documented levels of external debt. These hidden debts encompass domestic public debts (which prior to our data were largely undocumented)."